Does sex hormone treatment reverse the sex-dependent stress regulation? A longitudinal study on hypothalamus-pituitary-adrenal (HPA) axis activity in transgender individuals. (June 2019) - Fuss, Johannes; Claro, Lena; Ising, Marcus; Biedermann, Sarah V.; Wiedemann, Klaus; Stalla, Günter K.; Briken, Peer; Auer, Matthias K.
Highlights: We demonstrate long-term effects of sex hormone treatment on HPA-axis activity in humans. Estradiol treatment and testosterone withdrawal increase overall ACTH and cortisol secretion following CRH in transwomen. Testosterone treatment and estradiol withdrawal decrease overall ACTH and cortisol secretion following CRH in transmen. Testosterone treatment and estradiol withdrawal attenuate sensitivity for ACTH at the adrenal level in transmen. Overall cortisol secretion following CRH administration is strongly influenced by copeptin levels. Abstract: Background: Studies in mammals indicate a role for sex hormones in the regulation of hypothalamic–pituitary–adrenal (HPA)-axis reactivity. However, in humans, experimental paradigms investigating long-term exposure to sex hormones are sparse, limiting the understanding of the influence of sex hormones on HPA-axis activity. Gender-affirming hormone therapy (GAHT) in transgender persons enables to study the physiological role of sex steroids partially uncoupled from the distinct genetic background of men and women. Methods: Ten transwomen (male genotype and female gender identity) and 15 transmen (female genotype and male gender identity) were investigated at baseline and following three months of GAHT by means of the combined dexamethasone (dex)/CRH-test. Linear mixed-effects model analysis was used to assess changes over time and to identify determinants of HPA-axis reactivity. Results: In response to CRH, overall ACTH (+18%) as well as cortisol (+15%) output were increased in transwomen after 3-months of estrogen and antiandrogen treatment, while the opposite was the case for transmen after testosterone treatment (-15% and -58%, respectively). The ACTH/Cortisol-ratio indicated that testosterone attenuated sensitivity for ACTH at the adrenal level in transmen. Interestingly, copeptin levels before CRH administration were a strong predictor of overall cortisol secretion. Conclusions: This is the first study demonstrating long-term effects of a complete reversal of the sex-hormonal milieu on HPA-axis activity in humans. Our findings hereby expand the current knowledge of the physiology of HPA-axis regulation. and may be particularly relevant for transgender and cisgender people undergoing hormonal suppression or substitution therapies.